Modernizing through tradition: the current heraldry in the Spanish Army and its symbolic dimension as identification and diffusion of its institutional image - Medina Avila, Carlos J. (Eikón / Imago, 2025)
Heraldic symbols are one of the most relevant and identifying representations of the military sphere. At the end of the 1980s, the disorder in which military heraldry found itself in the Spanish Armed Forces made it necessary to regenerate it to recover its purity and its identifying purpose and, at once, modernize its institutional image. This article analyzes the various actions carried out through the regulation of the criteria for the design of coats of arms by applying the basic concepts of general heraldry, and the modernization of armories with the establishment and standardization of exterior ornaments, which began in the Army and was extended to the Navy and the Air Force, configuring the current heraldic panorama in the military institution.